Analysis of decentral platoon planning possibilities in road freight transport using an agent-based simulation model. Issue 1 (2nd January 2020) - Elbert, Ralf; Knigge, Jan-Karl; Friedrich, Anne
ABSTRACT: In this paper, a modelling approach is proposed in order to simulate platoon planning possibilities for individual trucks. An agent-based simulation model has been developed using a generic transport network with randomly generated transports in order to calculate potential waiting times of trucks for platooning possibilities. As expected, results show that waiting times decline when the number of orders and consequently the amount of trucks is increased in the network. Also, results indicate that waiting times at certain road sections especially in the network's periphery can be higher compared to sections in the centre, making them less suitable for trucks to wait at. Furthermore, an approach is proposed to calculate waiting time probabilities in order to integrate platooning possibilities into planning of truck routes. The model can be used to investigate decentralised platooning possibilities and analyse the trade-off between savings generated by platooning and the costs for necessary waiting times.